Melatonin Alleviates Venous Dysfunction in a Mouse Model of Iliac Vein Occlusion - Guo, Zhiye; Du, Xiaolong; Zhou, Yu; Xu, Dandan; Xu, Xingyu; Lu, Shan; Ran, Feng (Frontiers in Immunology, 2022)
The iliac vein can be severely stenosed and occluded due to thrombosis, tumor compression or anatomical abnormality. Such occlusion could result in limb swelling, venous claudication and persistent leg ulcers. Its devastating sequelae heavily impacts patients' lifestyles and social economy. Due to a lack of stable and easy-to-operate iliac vein occlusion (IVO) model, its underlying molecular mechanism and pathophysiological process has not been completely understood. Melatonin (MLT) plays critical roles in anti-inflammation, but the potential protective effect of melatonin on venous dysfunction induced by IVO has not been revealed. In this study, a mouse model of IVO was established to study the effects of MLT on injured veins. The results of laser speckle images and Evans blue showed that MLT inhibited venous permeability in IVO mouse model. Furthermore, MLT suppressed inflammation of surrounding tissues close to affected vein by inhibiting the mRNA levels of TNFα, IL-1 α and MCP-1. In addition, endothelial injury was inhibited by MLT using zonula occludens protein-1 (ZO-1) staining. Taken together, we elucidated the therapeutic effect of MLT on vascular dysfunction induced by IVO, mainly by inhibiting the TNFα, IL-1 α and MCP-1 mRNA levels, improving endothelial function and inhibiting vascular leakage.